Envolvimento de neurotransmissões angiotensinérgicas no núcleo medial da amídala nas respostas cardiovasculares e ansiogênica ao estresse de restrição em ratos - Costa-Ferreira, Willian (Universidade Federal de São Carlos, 2020)
Limbic structures participate in the control of physiological responses related to stress, and the medial amigdaloid nucleus (MeA) has been demonstrated as an area of the central nervous system involved in the control these responses. The angiotensin II, acting on the AT1 receptor, has been shown to be an important signaling mechanism in the central nervous system involved in the etiology of behavioral changes and in the physiological adjustments observed during aversive situations, whereas the AT2 receptor and the angiotensin 1-7/Mas receptor neutranmission acts as a mechanism against regulation of the AT1 receptor. Thus, the hypothesis of our work was that cardiovascular and anxiogenic changes to restraint stress (RS) are modulated by angiotensin II/ AT1 receptor, AT2 and angiotensin 1-7 / Mas receptor neurotransmission in the AMe. In the characterization the role of angiotensinergic neurotransmissions in the MeA in the baroreflex control activity in non-stressed animals indicated that the AT2 receptor in MeA plays an inhibitory role in the tachycardia reflex response, but without affecting bradycardia reflex; whereas the Mas receptor has a facilitating influence on both tachycardia and bradycardia reflex. In experiments on cardiovascular function of exposure to a 10-days of RS, this protocol caused an increase in arterial pressure baseline, facilitated tachycardic reflex and impaired spontaneous baroreflex activity. The animals treated with losartan attenuated tachycardia reflex, whereas the other changes were not affected by treatments. In the experiment comparing the effects of the MeA pharmacological treatments with angiotensinergic receptors agonists and antagonists on cardiovascular responses during an acute session and the 10th RS session, we found that repeated exposure to RS abolished facilitation of tachycardic response caused by the treatment of the MeA with angiotensin II and losartan in acute stressed animals. The tachycardic reduction caused by A-779 and the pressor response in animals treated with PD123319 in animals that were acutely stressed, was inhibited after repeated exposure to RS. In addition, repeated exposure to RS reversed the reduction in tachycardic response caused by MeA treatment with PD123319 seen in acutely stressed animals. Was not observed effect on facilitation of the tachycardic response after repeated exposure to RS by angiontensin 1-7 microinjection in the MeA. The reduction in the skin's tail temperature was greater in chronically stressed animals, and only treatment with PD123319 inhibited this facilitation. In the anxiogenic response, animals that went through an acute session showed behavioral of the anxiogenic type, and treatments with angiotensin II, losartan and angiotensin 1-7 inhibited this effect. Anxiogenic effect was also observed 24h after the 9th restraint session, and without additional five minutes after the 10th restraint session. In addition, the pharmacological treatments of the MeA did not cause any behavioral changes in the EPM in animals repeatedly exposed to RS. Finally, we identified that repeated exposure to RS increased the expression of the AT1 receptor and decreased the expression of the Mas receptor in the MeA. In short, our data support an involvement of RAS present in MeA in the control of cardiovascular and behavioral responses to stress, and this control seems to beinfluenced by previous experience with the stressor.
Involvement of angiotensinergic neurotransmission in the medial amygdaloid nucleus in cardiovascular and anxiogenic responses to restraint stress in rats
Keywords: Estresse; Estresse de restrição; Cardiovascular; Núcleo medial da amídala; Ansiedade; Angiotensina; Stress; Restraint stress; Medial amygdaloid nucleus; Anxiety; Angiotensin; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA